The effect of work facilities, discipline and comfort on employee performance at the secretariat of the regional people's representative council of Kerinci Regency - Wazirman Wazirman; Jufri Yeki; Juperma Juperma; Neneng Swir Mastuti (Institute of Computer Science (IOCS), 2023)
This study aims to see the effect of work facilities, work discipline and comfort on the performance of employees of the Kerinci Regency DPRD Secretariat both individually and collectively.The population in this study were all employees of the Kerinci Regency DPRD Secretariat of 35 people. The technique of determining the number of samples taken as respondents with this sampling technique uses the total sampling technique (overall sample). The reason for taking total sampling is because the total population is less than 100, the entire population is used as a research sample.The results of this study indicate that work facilities have a positive influence on employee performance at the Kerinci Regency DPRD Secretariat, work discipline has a positive influence on employee performance at the Kerinci Regency DPRD Secretariat, comfort has a positive influence on employee performance at the Kerinci Regency DPRD Secretariat and work facilities, work discipline and comfort together have a significant effect on the performance of employees of the Kerinci Regency DPRD Secretariat.